ANALISIS DAYA SAING EKONOMI KOTA BINJAI PROVINSI SUMATERA UTARA - Muhammad Sefti Arif Lubis; Paidi Hidayat (Ekonomi dan Keuangan, 2015)
The purpose of this study was to determine the factors determining economic competitiveness in Binjai 2014. Methods of data collection is done by purposive sampling method by distributing questionnaires. Data were analyzed by using Analytical Hierarchy Process (AHP).The analysis shows that there are three dominant factors affecting the competitiveness of the economy in Binjai city is a factor of physical infrastructure, regional economic factors and factors of labor and productivity. The main priority is to build the physical infrastructure to improve the quality of infrastructure. Then, to build the local economy his top priority is to optimize the economic potential of the region. Next to the main priority in building labor and productivity is to increase labor productivity.Keywords: Economic Competitiveness, Analytical Hierarchy Process (AHP)